2021
DOI: 10.3390/met11040584
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Deceleration Methods of Fatigue Crack Growth Rates under Mode I Loading Type in Pearlitic Rail Steel

Abstract: The paper presents a comparison of the results of the fatigue crack growth rate for raw rail steel, steel reinforced with composite material—CFRP—and also in the case of counteracting crack growth using the stop-hole technique, as well as with an application of an “anti-crack growth fluid”. All specimens were tested using constant load amplitude methods with a maximum loading of Fmax = 8 kN and stress ratio R = smin/smax = 0.1 in order to analyze the efficiency of different strategies of fatigue crack growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The closure of the crack was discussed in three articles [5][6][7]. Zakavi et al [5] presents new tools to evaluate the crack front shape of through-the-thickness cracks propagating in plates under quasi-steady-state conditions.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The closure of the crack was discussed in three articles [5][6][7]. Zakavi et al [5] presents new tools to evaluate the crack front shape of through-the-thickness cracks propagating in plates under quasi-steady-state conditions.…”
Section: Contributionsmentioning
confidence: 99%
“…A numerical approach incorporating simplified phenomenological models of plasticity-induced crack closure was developed and validated against experimental results. Lesiuk et al [6] showed a comparison of the results of the fatigue crack growth rate for raw rail steel, steel reinforced with composite material-CFRP-and the case of counteracting crack growth using the stop-hole technique, as well as with an "anti-crack growth fluid". It has been shown that the fatigue crack grows fastest in the case of the raw material and slowest in the case of the "anti-crack growth fluid" application.…”
Section: Contributionsmentioning
confidence: 99%
“…They are very similar, but rails made of steel R350HT additionally undergo thermal treatment and are characterized by better properties, thus finding more and more applications. In the past, most rails were made of R260 steel, and they are still tested for, among other things, fatigue [8] and white layer [9]. Recently, R350HT has been used more and more often, but the heat treatment process is complicated in the case of large-scale production.…”
Section: Introductionmentioning
confidence: 99%